Bioefficacy evaluation of different herbicides on weed population, grain yield and nutrient uptake in direct seeded puddled rice (Oryza sativa L.) - Nath, C.P.; Saha, M.; Pandey, P.C.; Das, T.K.; Meena, R.K.; Paul, T. (Annals of Agricultural Research, 2014)
The field study was conducted during kharif 2010 at N.E. Borlaug Crop Research Centre of G.B. PantUniversity of Agriculture and Technology, Pantnagar to evaluate the efficacy of different herbicides for direct seeded puddled rice. Nine weed control treatments were laid out in randomized block design with four replications. Results revealed that the major weed species in experimental site were Echinochloa colona L., Echinochloa crusgalli L., Cyperus rotundus L., Cyperus difformis L. Caesulia axillaris L. and Commelina benghalensis L. Grasses constituted the highest percentage (59.17) of weed population followed by broad leaves (23.85). Among the herbicides, lowest weed population was observed with the application of penoxsulam 25 g/ha at 30 and 90 DAS. The highest grain yield (4.56 t/ha) was recorded in weed free check treatment followed by two hand weeding treatment (4.09 t/ha) which was statistically at par with penoxsulam 25 g/ha, bispyribac sodium 25 g/ha and pyrazosulfuron ethyl 20 g/ha. All the weed control treatments caused significant reduction in uptake of nutrients by weeds over weedy check.